DESIGN OF A LOW VIBRATION GRINDING JIG AND FIXTURE FOR PIPE BEVELING PRIOR TO WELDING - Hussein, N.I.S.; Ayof, M.N.; Zainuddin, M.S.; Srithorn, J. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Pipes are commonly welded through various types of ends, including bevelled ends. Pipe bevelling is a process of forming an angle between the pipe end edge and the plane perpendicular to the surface. The pipe bevel angle depends on the welding standard, including angles such as 30° and 45°. The most convenient way to bevel a pipe in preparation for welding is by using the hand grinding process. Although it is the cheapest way to bevel a pipe, the problem of using a hand grinder is the least safe method of all and time consuming as well as requires skilled operations. Besides, the operator is exposed to vibration during the hand grinding process. The use of a vibrating hand-held grinding power tool is associated with vibration disease that may damage the vascular, sensory or musculoskeletal system. So far, however, limited design has focused on eliminating the vibration on a hand-held power tool. Where eliminating the problem could be challenging, better tool design may help reduce some vibration transmitted to the operator. Therefore, the objective of this study is to design a low vibration grinding jig and fixture system to bevel a pipe in preparation for welding. A pipe of 20 mm diameter is the focus of this design. The design process includes product design specification and conceptual design. Based on screening and scoring methods, the highest net score was 7 for concept design 3. Thus, concept design 3 was selected for the final design, which was technically drawn using Computer Aided Design (CAD) software. The findings of this study will propose a new design that will reduce vibration compared to the conventional method of beveling a pipe.